Assessing User’s Visual Attention on University Library Web Page with Eye Tracking Technology - Chih-Ming Chen; Hui-Ching Lin (Tūzī yǔ dàng’àn xuékān, 2015)
The establishment of domestic university library websites has currently reached 100%, web pages have become the most direct and rapid channels to market the academic resources, and advertisement on the library web pages is utilized for attracting readers' attention to activities. With true-experiment research method, the visual design of web pages to attract readers' attention in this study is integrated with the effects of visual elements on readers' visual behaviors. The design includes the identical advertising contents placed in three different positions on the index page of the library website to compare the differences in readers' visual attention. 54 undergraduate students are selected as the research participants. An eye tracker is utilized for collecting the participants' eye-tracking indicators, and the memory effect of the advertisement is tested. The questionnaire survey and interviews are also proceeded to discuss the effects of advertising positions on the index page of a university library website on readers' visual attention and memory effect. The research findings show the significant differences among the participants on the eye-tracking information, memory effect, browsing order, and overall satisfaction of the three advertisement positions. The participants pay more attention on top-layout advertisement, but stay the vision more on left-layout one. The results also reveal remarkable differences on memory effect of advertisement among three advertisement positions, where the optimal memory effect appears on the left-layout one.